“Cadáveres”: The staging of a sorrowful memory - Prieto Rodríguez, Adlin De Jesús (2017)
In Latin America there are various aesthetic practices that problematize the experience of loss, pain and address the materiality of bodily remains as a space for the response of regimes that regulate life: the corpse is in them the protagonist of the lived experience, the motor of questions and aesthetic formulations, as well as the horizon of political bets. From the approach of a founding text of neo-muddy poetry and the theme of the corpse in Latin America: “Cadáveres” (1981) by Néstor Perlongher, this article proposes a reflection on how aesthetics, from the poetic point of view, can give an account of a bereavement in suspense and can make a practice of mourning memory that confronts the arbitrary political ordering of bodies.